The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep44540
|View full text |Cite
|
Sign up to set email alerts
|

Raman Sensitive Degradation and Etching Dynamics of Exfoliated Black Phosphorus

Abstract: Layered black phosphorus has drawn much attention due to the existence of a band gap compared to the widely known graphene. However, environmental stability of black phosphorus is still a major issue, which hinders the realization of practical device applications. Here, we spatially Raman map exfoliated black phosphorus using confocal fast-scanning technique at different time intervals. We observe a Raman intensity modulation for , B2g, and modes. This Raman modulation is found to be caused by optical interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 39 publications
(44 reference statements)
3
61
1
Order By: Relevance
“…Oxidation effects have been thoroughly analyzed using Raman spectroscopy showing a systematic and continuous degradation of BP's Raman (A 1 g = 335 cm −1 , B 2g = 434 cm −1 , and A 2 g = 460 cm −1 ) signature as crystalline layers become oxidized ( Figure ). Since the oxidized layers do not contribute to the Raman signal, a significant decrease in peak intensities is observed with minimal shift in peak positions or full width at half maximum . Favron et al showed that the intensity ratio of the A 1 g /A 2 g modes could be an effective tool for detecting degradation .…”
Section: Stability and Passivationmentioning
confidence: 99%
“…Oxidation effects have been thoroughly analyzed using Raman spectroscopy showing a systematic and continuous degradation of BP's Raman (A 1 g = 335 cm −1 , B 2g = 434 cm −1 , and A 2 g = 460 cm −1 ) signature as crystalline layers become oxidized ( Figure ). Since the oxidized layers do not contribute to the Raman signal, a significant decrease in peak intensities is observed with minimal shift in peak positions or full width at half maximum . Favron et al showed that the intensity ratio of the A 1 g /A 2 g modes could be an effective tool for detecting degradation .…”
Section: Stability and Passivationmentioning
confidence: 99%
“…Moreover peak broadening is also observed which can be attributed to the size effects. On the other hand, upon nitrogen doping, A 1 g , B 2g , and A 2 g vibrational modes exhibit a red-shift of 9 cm −1 , 18 cm −1 and 8.3 cm −1 respectively featuring a phonon softening [14]. It is also important to recall that Raman spectroscopic analysis not only involves one phonon process known as first-order Raman scattering but also higher-order processes.…”
Section: Resultsmentioning
confidence: 99%
“…Since the stability of BP remains an issue before BP can be used for optoelectronic devices because of oxidation, confocal fast‐scanning Raman imaging was performed to map the layered black phosphorus during degradation. The effect of thickness owing to surface and edge degradation of black phosphorus was involved in the Raman intensity modulation, indicating the usefulness of poly(methyl methacrylate) (PMMA) passivation …”
Section: Microscale Spectral Mapping and Optical‐property Studiesmentioning
confidence: 99%